Surface macro‐fabric analysis of relict rock glaciers in the Cantabrian Mountains (NW Spain). (6th November 2019) - González‐Gutiérrez, R. Blanca; Santos‐González, Javier; Gómez‐Villar, Amelia; Redondo‐Vega, José M.
Abstract: Relict rock glaciers are widespread in the Cantabrian Mountains, with more than 250 lobate, tongued‐shaped and complex landforms identified. Located mostly within glacial cirques, facing north and northeast, these landforms are indicative of the distribution of ancient permafrost. Macro‐fabric analysis allows us to reconstruct the past dynamics of these landforms. Surface macro‐fabric analysis of 34 rock glaciers including both ridge and furrows was performed. The orientation and dip of 50 clasts was determined in each case. All data were plotted in equal‐area stereograms and the eigenvalue method was used for statistical analysis of the data. The data show weak fabric shapes, with the transitional and the girdle shapes being the most representative, with 67.6% of the samples studied. The main fabric direction (eigenvalue S1 ) is found in 40–60% of the clasts, and only 11.7% present values ≥0.60. Clast concentration density in the stereograms gives concentrations <10% in more than 73.5% of the samples. Ridge samples have a more intense fabric than those of the furrows. The tongue‐shaped rock glaciers show more diverse values than those with lobate and complex forms.